Analisis Strategi Pemasaran Digital dalam Meningkatkan Keunggulan Bersaing UMKM Baso Aci Nyerenteng - Nur Diansyah; Arie Hendra Saputro (Ikatan Da'i Indonesia, 2026)
This study aims to analyze digital marketing strategies for enhancing the competitive advantage of Baso Aci Nyerenteng Micro, Small, and Medium Enterprise (MSME) using a SWOT analysis approach. The research employed a qualitative method with a case study approach to gain an in-depth understanding of the implementation of digital marketing strategies within the enterprise. Data were collected through observation, documentation, and literature review, supported by scientific journals, books, and official publications. Data analysis was conducted descriptively using the SWOT matrix by identifying internal factors, including strengths and weaknesses, as well as external factors consisting of opportunities and threats, to formulate appropriate marketing strategies. The findings indicate that Baso Aci Nyerenteng possesses several competitive strengths, including its authentic Garut flavor, diverse product offerings, competitive pricing, and the utilization of digital platforms such as Shopee, Instagram, TikTok, and Google Business Profile for marketing activities. However, the business also faces several challenges, including limited brand awareness, constrained capital and production capacity, and inconsistent digital promotional activities. The SWOT analysis resulted in four strategic alternatives: optimizing social media content marketing, strengthening brand awareness, developing reseller and affiliate marketing programs, enhancing customer service through digital platforms, and improving operational efficiency and business legality. The implementation of these strategies is expected to increase product visibility, expand market reach, strengthen customer loyalty, and create a sustainable competitive advantage for Baso Aci Nyerenteng.